منهج الحافظ ابن كثير في التعامل مع الأحاديث الضعيفة من خلال تفسيره - شنوف, عبد الهادي (University of eloued جامعة الوادي, 2016)
الحمد لله وكفى والصلاة والسلام على الرسول الدصطفى يقوم ىذا البحث بدراسة جانب من الجوانب الحديثية لدنهج الحافظ ابن كثير في تفسيره، فجاء بعنوان: " منهج الحافظ ابن كثير في التعامل مع الحديث الضعيف في تفسيره ". ولقد اِنْبَنََ من مقدمة وثلاثة فصول وخاتمة، خصصت الدقدمة لذكر أهمية الدوضوع وطرح إشكالياتو، وذكر أسباب اختياره والأىداف الدرجوة منو، وذكر الدراسات السابقة لذذا الدوضوع. أما الفصل الأول فكان كتمهيد للموضوع تكلمت فيو عن ترجمة الحافظ ابن كثير ومنهجو في كتابو التفسير. وخصصت الفصل الثاني للحديث عن الجانب النظري من خلال تعريف الحديث الضعيف وذكر أبرز مسالك الضعف إلى الحديث وحكم الاحتجاج بالحديث الضعيف. لأتحدث في الفصل الأخير عن طريقة الحافظ ابن كثير في التعامل مع الأحاديث الضعيفة في تفسيره. وذكرت في الخاتمة أبرز النتائج والتوصيات التي توصلت إليها من خلال ىذا البحث. وقد خلص البحث إلى جملة من النتائج أهمها: أن الحافظ ابن كثير محدث ناقد، طبق قواعد المحدثين عند تعاملو مع الحديث الضعيف في تفسيره، وكان ذو منهج وسط مزج بين دقة الدتقدمين واطلاع الدتأخرين. وصلى الله وسلم عل سيدنا محمد.This research studies one of the Hadith side at the interpretation of El-Hafed Ben Katheer, so that we entitled it "Ben katheer's method in dealing with weak Hadeeths". This research contains of an introduction , three chapters and a conclusion; the introduction was devoted to indicating the importance of the subject and explaining the problematic, the reasons of selecting of the subject, the desired objectives and previous studies. The introductory chapter was specified to biography of Ben Katheer and his style in interpretation books. While the second chapter was a theoretical side including the definition of weak Hadeeth and the most know ways of weakness and the verdict of its inference. However the third chapter focuses on the mothed of Ben Katheer in dealing with weak Hadiths in his interpretation. Finally, a conclusion containing the important results and recomendations. We have reached in this research that El-hafed Ben Katheer was critic scholars of prophet's Hadeeth who applied the previous scholars ways in dealing with unreliable Hadeeth in his interpretation, hence he has a moderate way involving the former's accuracy and the subsequent's acquaintance
ماستر علوم الحديث
Keywords: منهج الحافظ ابن كثير,التعامل,الأحاديث الضعيفة,تفسير; The approach of Al-Hafiz Ibn Kathir, dealing with weak hadiths, interpretation